Nanoscale markers of esophageal field carcinogenesis: potential implications for esophageal cancer screening - Konda, Vani JA; Cherkezyan, Lusik; Subramanian, Hariharan; Wroblewski, Kirsten; Damania, Dhwanil; Becker, Valentin; Gonzalez, Mariano Haba Ruiz; Koons, Ann; Goldberg, Michael; Ferguson, Mark K; Waxman, Irving; Roy, Hermant K; Backman, Vadim (Endoscopy, 2013)
Background and study aims: Esophageal adenocarcinoma (EAC) has a dismal prognosis unless treated early or prevented at the precursor stage of Barrett’s esophagus-associated dysplasia. However, some patients with cancer or dysplastic Barrett’s esophagus (DBE) may not be captured by current screening and surveillance programs. Additional screening techniques are needed to determine who would benefit from endoscopic screening or surveillance. Partial wave spectroscopy (PWS) microscopy (also known as nanocytology) measures the disorder strength (Ld), a statistic that characterizes the spatial distribution of the intracellular mass at the nanoscale level and thus provides insights into the cell nanoscale architecture beyond that which is revealed by conventional microscopy. The aim of the present study was to compare the disorder strength measured by PWS in normal squamous epithelium in the proximal esophagus to determine whether nanoscale architectural differences are detectable in the field area of EAC and Barrett’s esophagus.Methods: During endoscopy, proximal esophageal squamous cells were obtained by brushings and were fixed in alcohol and stained with standard hematoxylin and Cyto-Stain. The disorder strength of these sampled squamous cells was determined by PWS.Results: A total of 75 patient samples were analyzed, 15 of which were pathologically confirmed as EAC, 13 were DBE, and 15 were non-dysplastic Barrett’s esophagus; 32 of the patients, most of whom had reflux symptoms, acted as controls. The mean disorder strength per patient in cytologically normal squamous cells in the proximal esophagus of patients with EAC was 1.79-times higher than that of controls (P < 0.01). Patients with DBE also had a disorder strength 1.63-times higher than controls (P < 0.01).Conclusion: Intracellular nanoarchitectural changes were found in the proximal squamous epithelium in patients harboring distal EAC and DBE using PWS. Advances in this technology and the biological phenomenon of the field effect of carcinogenesis revealed in this study may lead to a useful tool in non-invasive screening practices in DBE and EAC.